Reuse of computer systems in Bulgaria – analysis of market trends - Petrov, Georgi; Mitov, Borislav (Annual of Natural Sciences Department, 2025)
The analysis explores the growth of the used computer systems market in Bulgaria, highlighting economic and environmental benefits such as savings and reduced electronic waste. The system integration market is also growing due to European programs, with a focus on innovation and cybersecurity. Challenges in the used equipment market include technical issues and limited compatibility, but it remains attractive to small and medium-sized enterprises.